Exposição ocupacional a pesticidas e sua relação com a desregulação imunológica em pacientes com câncer de mama - Santos, Stephany Bonin Godinho dos (2022)
Breast cancer is the most frequent neoplasm in women, it does not have a single cause, but 80% to 90% of cases are associated with external causes, which are the so-called environmental factors, including exposure to pesticides. The aim of this study was to investigate occupational exposure to pesticides and the relationship with immunological dysregulation of cytokines in breast cancer patients. The methodological procedures are divided into two stages. The first step consists of a systematic review on the topic: pesticides, immune disorders and cancer, based on the PRISMA guidelines and the PICO strategy. The second stage consisted of an original study. This is a retrospective and prospective study with a selection of 187 women with breast cancer, 111 occupationally exposed to pesticides and 71 not exposed, all treated at the Francisco Beltrão Cancer Hospital (CEONC) from 2015 to 2021. The patients were divided according to clinicopathological profile, based on immunohistochemical expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), Ki-67 proliferation index, tumor size, histological grade, intratumoral embolus, presence of axillary lymph node metastases, distance to metastasis, age at diagnosis (defined as early or late), menopausal status, body mass index (BMI), recurrence, metastasis sites, and survival profile. A profile of the patients' plasma cytokines was performed, through the measurement of interleukin 1β (IL-1β), interleukin 12 (IL-12), interleukin 4 (IL-4), interleukin 17 A (IL-17-A) and factor of tumor necrosis – alpha (TNF-α). As partial results, in the systematic review few studies were found in humans in relation to the proposed topic. In the original research, in relation to the clinicopathological profile, comparing the patients of the two groups, it is possible to verify that the most aggressive molecular subtype, TN, had a higher percentage among women exposed to pesticides (29.58%), being double that of the women exposed to pesticides (29.58%). not exposed (14.08%). Another point was the metastasis in lymph nodes, and the variable of at least one affected lymph node was 10% higher in exposed women (34.23%) compared to non-exposed women (23.94%). Another feature was that 5% more women exposed to pesticides had a higher BMI, indicating overweight or obesity. Regarding the plasma profile of cytokines, no statistical difference was found between the means of the groups exposed and not exposed to pesticides. However, when these cytokines were compared individually with each variable of the clinicopathological profile, it was possible to identify an immunological dysregulation, where in some specific conditions, patients exposed to pesticides had a lower value of circulating plasma cytokine in relation to those not exposed, indicating a drop in Th17 profile response, for: Luminal B, Ki67>14%, Histological Grade 3, ER and eutrophic patients. In the Th1 profile for: tumor size and lymph node invasion present, in the latter, the value of Th2 cytokines was also lower among exposed individuals compared with non-exposed individuals.